KOMBINASI KOMPOS JERAMI PADI DAN PUPUK NPKMg UNTUK PERTUMBUHAN BIBIT KELAPA SAWIT DI PEMBIBITAN UTAMA - Nurfadilla, Nurfadilla; Gusniwati, Gusniwati; Neliyati, Neliyati; Kartika, Elis (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2026)
Oil palm is one of Indonesia’s major plantation commodities and plays an important role as a source of national foreign exchange. The decline in oil palm productivity due to the high proportion of damaged and unproductive plants has increased the need for replanting supported by the production of high-quality seedlings. The success of seedling production is influenced by growing media and fertilization, particularly in Ultisol soils, which are characterized by low organic matter content. This study aimed to evaluate the growth response of oil palm seedlings to the application of rice straw compost and NPKMg fertilizer and to determine the best treatment combination in the main nursery. The experiment was conducted for three months using a Completely Randomized Design (CRD) with five treatments: p0 = 100% of the recommended dose of NPKMg p1 = 200 g rice straw compost + 50% of the recommended dose of NPKMg; p2 = 250 g rice straw compost + 50% of the recommended dose of NPKMg; p3 = 300 g rice straw compost + 50% of the recommended dose of NPKMg; and p4 = 350 g rice straw compost + 50% of the recommended dose of NPKMg, with four replications. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% significance level. The results showed that the combination of rice straw compost and NPKMg fertilizer improved seedling height and shoot dry weight, whereas leaf number, stem diameter, root dry weight, shoot-to-root ratio, and seedling quality index did not improve. The application of 250 g rice straw compost combined with 50% of the recommended dose of NPKMg (15-15-6-4) was the best treatment and produced seedling growth comparable to that obtained with the 100% recommended dose of NPKMg. Therefore, this combination is recommended as an alternative to reduce the use of inorganic fertilizer by up to 50%.